Pengaruh Prinsip Ekonomi Islam terhadap Keputusan Trading Cryptocurrency Oleh Traders Muslim Dalam Komunitas New Crypto Jambi Dan Exness Trading Di Kota Jambi - Fikry Ramadhani Hasan; Lucky Enggrani Fitri; Ary Dean Amri (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the influence of Islamic economic principles on the cryptocurrency trading decisions of Muslim traders in the New Crypto Jambi and Exness Trading communities in Jambi City. The research findings show that the understanding of Islamic economic principles among Muslim traders is still low, both in the novice community (New Crypto Jambi) and the experienced community (Exness Trading). The majority of traders focus more on financial profit without considering the Islamic aspects in their trading decisions. The Exness Trading community tends to be more cautious in selecting trading instruments, although they are still uncertain about the legality of their activities. Meanwhile, traders in the New Crypto Jambi community tend to overlook the consideration of Islamic law in their trading activities and only become aware of Islamic principles after experiencing losses. Additionally, most traders do not understand the elements of gharar, maysir, and riba in cryptocurrency and have not made efforts to seek legal clarification through fatwas from scholars or Shariah financial institutions. In conclusion, the influence of Islamic economic principles on trading decisions is still very minimal due to the lack of Islamic economic literacy, limited education, and the weak role of communities in disseminating Sharia principles. This study recommends increasing Islamic economic literacy through collaboration with Shariah economic experts, as well as organizing regular discussions in trading communities on halal-haram principles in cryptocurrency trading. Further research with direct observation and in-depth interviews is recommended to explore the influence of religiosity perceptions on trading decisions.